2016
DOI: 10.1142/s0217751x16440061
|View full text |Cite
|
Sign up to set email alerts
|

Probing the nonunitarity of the leptonic mixing matrix at the CEPC

Abstract: The non-unitarity of the leptonic mixing matrix is a generic signal of new physics aiming at the generation of the observed neutrino masses. We discuss the Minimal Unitarity Violation (MUV) scheme, an effective field theory framework which represents the class of extensions of the Standard Model (SM) by heavy neutral leptons, and discuss the present bounds on the non-unitarity parameters as well as estimates for the sensitivity of the CEPC, based on the performance parameters from the preCDR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…In ref. [3,12,53,54] it was shown that the FCC-ee and the CEPC are sensitive to sterile neutrino masses up to about 60 and 40 TeV, respectively, via the combination |θ e | 2 + |θ µ | 2 , using eq. (3) for neutrino Yukawa couplings O(1).…”
Section: Indirect Searches Via Electroweak Precision Observablesmentioning
confidence: 99%
“…In ref. [3,12,53,54] it was shown that the FCC-ee and the CEPC are sensitive to sterile neutrino masses up to about 60 and 40 TeV, respectively, via the combination |θ e | 2 + |θ µ | 2 , using eq. (3) for neutrino Yukawa couplings O(1).…”
Section: Indirect Searches Via Electroweak Precision Observablesmentioning
confidence: 99%
“…1 The elements of η αβ are constrained from the mass of the W boson, the Weinberg angle, muon decay rate, lepton-flavour-violating processes etc. at the level of 10 −3 to 0.05 [64][65][66][67][68]. The non-unitarity η modifies oscillation probabilities as a combination of the NSIs [65,69], and the size of the ε parameters induced by the non-unitarity effect corresponds in general to the order of η.…”
Section: Non-unitaritymentioning
confidence: 98%
“…In the presence of , the mixing matrix N is not unitary [93][94][95][96]. Considering the mass eigenstates, the charged current interaction in the Standard Model is given by…”
Section: Model and The Production Modementioning
confidence: 99%